PENGELOLAAN DAN PENGOLAHAN SAMPAH PADA MASYARAKAT SEKITAR KAMPUS 2 UNAND, PAYAKUMBUH - Bintang Rizky Abdullah Majo Saibah; Winny Alna Marlina; Ranny Fitriana Faisal; Agestayani Agestayani; Erizal Erizal; Susiana Susiana; Musbatiq Srivani; Faisal Ali Ahmad; Jauharry Jauharry (Jurnal Hilirisasi IPTEKS, 2018)
Environmental, economic and social aspects are three important pillars in sustainable development. However, the 2017 West Sumatra Environmental Management Regional Performance Document (DIKPLHD) stated that the waste generation in West Sumatra reached 2,452,213 kg / day and only 34.54% of districts / cities had managed the waste properly. So far, the handling of waste is usually conducted by stacking, collecting, and transporting to the Final Processing Site (TPA). Therefore, it is important to start a systematic program to reduce waste. One possible method that can be implemented is the empowerment of the waste bank. Campus 2 UNAND Payakumbuh has conducted community service through socialization and training programs with the theme "Turning Waste Into Rupiah". The objective of this program is to educate the public to be able to reduce waste in order to reach sustainable business development. In this training, the participants were provided with knowledge about waste management and the added value of recycling unused newspapers into useful items such as flower vases.